The Implementation of Advance Pricing Agreement in Indonesia Following The Adoption of Dispute Resolution Guideline - Oktaviani, Dealia Tiara; Tambunan, Maria R.U.D (UI Scholars Hub, 2021)
Advance Pricing Agreement (APA) is one of the fiscal instruments for minimizing transfer pricing disputes. In Indonesia, the regulation of APA was initially adopted in Income Tax Law year 2000 art 18(3a). Later, the implementation regulation was issued through Directorate General of Taxes Regulation, PER No. 69/PJ/2010. However, during that period the implementation of APA in Indonesia was still on very low progress. In 2015 Directorate General of Taxation (DGT) has not concluded to agree on any APA until the last revision of APA rule through Minister of Finance Regulation No 7/PMK.03/2015. This research utilizes a descriptive qualitative methodology where data is collected through a review of the literature and semi-structured in-depth interviews with key stakeholders. The result of this research shows that the development of APA implementation after the issuance of Minister of Finance Regulation No 7/PMK.03/2015 has increased. Based on statistics of APA in Indonesia after 2016 there was an increase in the APA submissions and the DGT has successfully concluded some APAs. The latest APA implementation in Indonesia has followed the dispute resolution guidelines as proposed by the Organization for Economic Cooperation and Development (OECD) through Base Erosion and Profit Shifting (BEPS) project as proposed in the Action Plan 14. However, there are issues pertaining to the implementation of APA such as transparency and certainty related to the APA process. Responding to these issues the DGT has made several attempts such as, improving human resources and strengthening the regulatory.